Highly Efficient Cyclic Dinucleotide Based Artificial Metalloribozymes for Enantioselective Friedel–Crafts Reactions in Water. Issue 9 (22nd January 2020) - Wang, Changhao; Hao, Min; Qi, Qianqian; Dang, Jingshuang; Dong, Xingchen; Lv, Shuting; Xiong, Ling; Gao, Huanhuan; Jia, Guoqing; Chen, Yashao; Hartig, Jörg S.; Li, Can
Abstract: The diverse secondary structures of nucleic acids are emerging as attractive chiral scaffolds to construct artificial metalloenzymes (ArMs) for enantioselective catalysis. DNA‐based ArMs containing duplex and G‐quadruplex scaffolds have been widely investigated, yet RNA‐based ArMs are scarce. Here we report that a cyclic dinucleotide of c‐di‐AMP and Cu 2+ ions assemble into an artificial metalloribozyme (c‐di‐AMP⋅Cu 2+ ) that enables catalysis of enantioselective Friedel–Crafts reactions in aqueous media with high reactivity and excellent enantioselectivity of up to 97 % ee . The assembly of c‐di‐AMP⋅Cu 2+ gives rise to a 20‐fold rate acceleration compared to Cu 2+ ions. Based on various biophysical techniques and density function theory (DFT) calculations, a fine coordination structure of c‐di‐AMP⋅Cu 2+ metalloribozyme is suggested in which two c‐di‐AMP form a dimer scaffold and the Cu 2+ ion is located in the center of an adenine‐adenine plane through binding to two N7 nitrogen atoms and one phosphate oxygen atom. Abstract : Fake it till you make it : A cyclic dinucleotide based artificial metalloribozyme assembled from c‐di‐AMP and Cu 2+ ions catalyzes enantioselective Friedel–Crafts reactions with high reactivity and excellent enantioselectivity.